Organic Nanoparticle-Based Combinatory Approaches for Gene Therapy. Issue 12 (December 2017) - Singh, Brahma N.; Prateeksha,; Gupta, Vijai K.; Chen, Jieyin; Atanasov, Atanas G.
Abstract : Engineered organic nanoparticle (ONP)-mediated co-delivery of genes and therapeutic agents is emerging as a powerful tool in the treatment of several genetic and non-genetic disorders. The ONP-based combinatory approach provides a technological platform that delivers genes with chemo/radio/photo/immunotherapies for the prevention or treatment of disease progression.